CORRECTION OF STRESS-INDUCED CHANGES OF MOTOR FUNCTION OF DUODENUM AND JEJUNUM DURING IMMOBILIZATION STRESS BY ANTIOXIDANT DRUGS (EXPERIMENTAL STUDY) - L. I. Korytov; M. I. Suslikova (Acta Biomedica Scientifica)
In chronic experiments on dogs the authors studied the dynamics of the contractile activity of duodenum and jejunum on the background of a course of antioxidant drug 2-ethyl-6-methyl-3-hydroxypyridine succinate in the daily one-hour immobilization stress. It has been found that antioxidant course administration chronic stress leads to the approximation increased contractile activity index duodenum and jejunum to the level of control data at an earlier date than under stress without the use of medication (on the 7th day of immobilization).